Momentaufnahme. - Anderson, Sascha; Boehm, Gottfried; Geccelli, Johannes; Growe, Bernd; Haftmann, Werner; Langner, Johannes; Ohff, Heinz; Roters, Eberhard; Schmied, Wieland; Wulffen, Thomas; Staatliche Kunsthalle, Berlin (Berlin : Staatliche Kunsthalle Berlin, 1987)
Armando ; Bachmann, Hermann ; Barfuss, Ina ; Blum, Eberhard ; Bubenik, Gernot ; Camaro, Alexander ; Diehl, Hans-Jürgen ; Fehrenbach, Gerson ; Geccelli, Johannes ; Girke, Raimund ; Hacker, Dieter ; Heinisch, Barbara ; Ter Hell ; Henkel, Manfred ; Höch, Hannah ; Hödicke, Karl Horst ; Hofer, Karl ; Kerbach, Ralf ; Köthe, Fritz ; Krauth, Hermann ; Kriester, Rainer ; Leiberg, Helge ; Meidner, Ludwig ; Musil, Robert ; Neumann, Max ; Odious, Gruppe ; Petrick, Wolfgang ; Pods, Reinhard ; Rheinsberg, Raffael ; Roters, Eberhard ; Ruckhaberle, Dieter ; Ruschmeyer, Heike ; Scheffler, Wolfram ; Scheib, Hans ; Schleime, Cornelia ; Schönebeck, Eugen ; Sorge, Peter ; Stöhrer, Walter ; Thieler, Fred ; Uhlmann, Hans ; Vogel, Stefanie ; Vogelgesang, Klaus ; Vostell, Wolf ; Wachweger, Thomas ; Williams, Emmett
biog., ind. tent., gr. tent. per kunstenaar
Duits
Momentaufnahme, Staatliche Kunsthalle Berlin, 25. April bis 12. Juli 1987
boek